Genocide and the politics of memory : studying death to preserve life - Hirsch, Herbert, 1941- (Chapel Hill : University of North Carolina Press, 1995)
A study into repetitions of large-scale human violence throughout history. It suggests that if we begin to understand how and why these episodes occur, we will be able to act to prevent them. To revise the politics of memory, proposals for essential reforms of the political state are made.
Politics, memory, and mass death -- Studying death -- Epilogue: Memory, hope, and triumph over evil.
Includes bibliographical references (pages 217-236) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Genocide; Memory -- Social aspects; Social conflict -- Psychological aspects; SOCIAL SCIENCE -- Demography; Genocide; Memory -- Social aspects; Social conflict -- Psychological aspects; Völkermord; Gedächtnis; Genocide; Criminology, Penology & Juvenile Delinquency; Social Welfare & Social Work; Social Sciences; Genocide